Performance Analysis of Advanced Encryption Standards for Voice Cryptography with Multiple Patterns - Hazzaa F.; Qashou A.; Al Barazanchi I.I.; Sekhar R.; Shah P.; Bachute M.; Abdulbaqi A.S. (International Information and Engineering Technology Association, 2025)
The aim of this research is analyzing its performance to help network designers to decide the suitable security solution for their network. Moreover, performance evaluation performance indicators that can be used to evaluate AES include; the encryption and decryption time, the CPU usage and how well AES performs on different platforms. Software performance indicators also take into account the analysis of throughput, latency, and energy consumption of the systems with special focus on software and hardware sections. Issues that have been noted when it comes to assessment of AES actually include the issue of security and performance, a challenge in managing-keys and finally the issue of platform heterogeneity. Analyzing the given result, it can be stated that there does not exist significant distinctions in the parameters related to the encryption process, including execution time and energy consumption, taking into account different patterns of voice. Thus, the performance analysis of AES for voice encryption and decryption is important to properly manage the scarce resources, to improve the security measures, to make the needed adjustments for further system scalability, to take into consideration the costs and make proper decisions to follow legal requirements encountered in communication systems. This work will be exploited in our upcoming research to enhance AES performance by developing new encryption algorithm. ? 2024 The authors.